Immediate adverse reactions to intravenous iodinated contrast media in computed tomography Reacciones adversas inmediatas al contraste yodado intravenoso en tomografía computarizada Reações adversas imediatas ao contraste iodado intravenoso em tomografia computadorizada - Beatriz Cavalcanti Juchem; Clarice Maria Dall'Agnol (Universidade de São Paulo, 2007)
This exploratory-descriptive, non-experimental quantitative research aimed to learn about immediate adverse reactions to intravenous iodinated contrast media in hospitalized patients submitted to computed tomography at a teaching hospital in the South of Brazil. During the study period, all adverse reactions showed mild intensity, at a frequency of 12.5% with ionic iodinated contrast media, and 1% with non-ionic contrast agent. The extravasation of contrast occurred in 2.2% of the injections in a peripheral vein without complications in any of the cases. The results are within the limits cited in international literature and suggest that tomography service professionals should know their own rates of adverse reactions to iodinated contrast agent, as well as the conditions in which they occur, in order to obtain evidence to evaluate the respective care delivery processes. Investigación cuantitativa del tipo exploratorio-descriptivo, de carácter no experimental. El objetivo consistía en conocer las reacciones adversas inmediatas al contraste yodado intravenoso en pacientes internados, sometidos a tomografía computarizada en un hospital escuela del sur de Brasil. Durante el período del estudio, todas las reacciones adversas tuvieron intensidad leve y una frecuencia del 12,5% con la utilización del contraste yodado iónico, y 1% con contraste no iónico. La extravasación del contraste ocurrió en un 2,2% de las inyecciones en vena periférica, no ocasionando complicaciones en ninguno de los casos. Los índices evidenciados en el presente estudio se mantuvieron dentro de los límites que constan en la revisión de literatura y, entre las recomendaciones, se sugiere que los servicios de tomografía conozcan los propios índices de reacciones adversas al contraste yodado y las condiciones en que ocurren, con la finalidad de obtener evidencias para evaluación de los respectivos procesos asistenciales. Pesquisa quantitativa, exploratório-descritiva, de caráter não experimental, com o objetivo de conhecer as reações adversas imediatas ao contraste iodado intravenoso em pacientes hospitalizados, submetidos a tomografia computadorizada num hospital-escola no Sul do Brasil. Durante o período de estudo, todas as reações adversas manifestaram-se na intensidade leve, com freqüência de 12,5% com o uso de contraste iodado iônico e 1% com contraste não iônico. Extravasamento do meio radiopaco ocorreu em 2,2% das injeções em veia periférica, não havendo complicações em nenhum dos casos. Os resultados encontram-se dentro dos limites citados na literatura internacional e sugere-se que os serviços de tomografia conheçam as próprias taxas de reações adversas ao contraste iodado e as condições em que elas ocorrem, a fim de obter evidências para a avaliação dos respectivos processos assistenciais.